Scenarios of the Near Future: Sustainable Development, Retreat or Collapse and Regeneration? - Nováček , Pavel (Studia Ecologiae et Bioethicae, 2024)
The elementary “map of the near future” could consist of three basic scenarios: sustainable development; sustainable retreat; or collapse and regeneration. Sustainable development remains the most serious attempt at finding an answer to the question of how to allow all people and nations to develop and improve their quality of life, while preserving functional ecosystems and a healthy environment for humankind. James Lovelock was the first to articulate the idea that it is too late for sustainable development and that we should strive for sustainable retreat. For Lovelock, the deadliest issue is the ongoing climate change, as it is irreversible and only can be mitigated. Sustainable retreat is hard to enforce politically and difficult to absorb mentally. Collapse of a civilization is a decrease in population size or political, economic, and social complexity over a large area for a long time. The collapse of a society does not usually come in the form of a sudden and apocalyptic downfall. Whether a society collapses or not depends on the society´s response to its problems and its capacity to solve them. A collapse is usually followed by rebirth and regeneration. This is a pattern in nature. Human society has followed a similar trend. Regardless how big a crisis is, it always presents an opportunity for catharsis and hope for a new beginning. However, there is no guarantee of the results.